Hereditary hemorrhagic telangiectasia: genetics and molecular diagnostics in a new era - McDonald, Jamie; Wooderchak-Donahue, Whitney; VanSant Webb, Chad; Whitehead, Kevin; Stevenson, David A.; Bayrak-Toydemir, Pinar (Frontiers in Genetics, 2015)
Hereditary hemorrhagic telangiectasia (HHT) is a vascular dysplasia characterized by telangiectases and arteriovenous malformations (AVMs) in particular locations described in consensus clinical diagnostic criteria published in 2000. Two genes in the transforming growth factor-beta (TGF-β) signaling pathway, ENG and ACVRL1, were discovered almost two decades ago, and mutations in these genes have been reported to cause up to 85% of HHT. In our experience, approximately 96% of individuals with HHT have a mutation in these two genes, when published (Curaçao) diagnostic criteria for HHT are strictly applied. More recently, two additional genes in the same pathway, SMAD4 and GDF2, have been identified in a much smaller number of patients with a similar or overlapping phenotype to HHT. Yet families still exist with compelling evidence of a hereditary telangiectasia disorder, but no identifiable mutation in a known gene. Recent availability of whole exome and genome testing has created new opportunities to facilitate gene discovery, identify genetic modifiers to explain clinical variability, and potentially define an increased spectrum of hereditary telangiectasia disorders. An expanded approach to molecular diagnostics for inherited telangiectasia disorders that incorporates a multi-gene next generation sequencing (NGS) HHT panel is proposed.